KONTRIBUSI SAREKAT ISLAM DALAM MEMBENTUK MASYARAKAT MADANI MELALUI PENDIDIKAN - Mansur Mansur (State Institute of Islamic Studies (IAIN) Salatiga, 2013)
This research will examined the purpose and principles of the Sarekat Islameducation and the education of Sarekat Islam (SI) empowering communitie.This research is the field research with qualitative data. Method of collectingthe data through observation, documentation, interviews, and libraries research. The data analysis will in the form of reflective thinking, deduction and induction. The findings of this study shows of education embodies a true muslim and a nationalis. Educational principles of instilling a sense of nationality, democracy, courage, a simple life, uphold degrees, selfreliance, and the integration of science of religion. finally the SI has been contributing about education system which was later used in the regulation of the education system in Indonesia.